Efecto de la adición de aceite de canela (cinnamomum zeylanicum) en la alimentación de cerdos postdestete sobre los parámetros productivos - Moreira Hernández, Dagner Eduardo (2022)
The objective of this thesis was to evaluate the effect of the addition of cinnamon oil (Cinnamomum zeylanicum) in the productive parameters in the feeding of pigs at weaning. 24 Landrace x Pietrain pigs were used which were designated to a DCA, with 3 treatments (T0: Control treatment; T1 Addition of 1% cinnamon oil and T2 Addition of 2% cinnamon oil) and 8 repetitions. The data were analyzed through an analysis of variance, using the 5% Tukey test with the statistical package InfoStat (2019). In the evaluation of the productive variables, it was found that there are no significant differences (P> 0.05), in which T2 stood out regarding weekly weight (44.77 kg ± 0.07) and weight gain weekly accumulated T0 (31.65 kg ± 0.17) and feed conversion (1.45); T1 achieved a higher feed intake (46.16 kg ± 0.07). It was found that the microbiological load of Escherichia coli and Salmonella spp. of pigs decreased with the addition of cinnamon oil in the feed. In the cost / benefit analysis, a higher income was found in animals that were not administered cinnamon oil, which for each dollar invested achieved a benefit of $ 1.19. It is concluded that the feeding of post-weaning pigs with the addition of cinnamon oil in the feed did not detract from the productive variables of the diets supplied and could be used to reduce the bacterial load in pigs without affecting health.